METHODOLOGY OF USING ACTIVITY GAMES IN PRIMARY CLASS PHYSICAL EDUCATION LESSONS (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article will talk about the overall description of action games, the variety and the improvement of the effectiveness of assistance, which has a pedagogical value that is supported in the educational process.